How an Organization Should Implement Risk Communication in Response to Cyber Attack in Indonesia - Syifa Astasia Utari; Velda Ardia; Jamiati Jamiati; Della Fitria (Journal on Education, 2023)
The escalation of internet use in Indonesia is directly proportional to the increase in the vulnerability of cyber attacks that have the potential to create a crisis. When an attack occurs, proper handling is required, not only in terms of technical aspects related to cyber operational systems, but also in aspects related to reputation and public trust. Public Relations plays an important role in carrying out the communication function when a crisis due to cyber attacks occurs, to maintain good relations and maintain public trust in affected organizations. This study seeks to provide recommendations on how public relations practitioners provide communication responses when crises due to cyber attacks occur. Using a literature-based explorative research method. Research shows that public relations practice is an important thing to do, especially in carrying out the communication function. Public relations must be responsive and have high awareness in carrying out early detection of potential crises due to cyberattacks, designing response plans, and conducting transparent, credible and accountable communications in order to maintain public trust and organizational reputation.